PENGARUH PEMUPUKAN TERHADAP PERTUMBUHAN DAN HASIL KEDELAI PADA LAHAN BEKAS TAMBANG, DI BANGKA TENGAH - Adhe Phoppy Etika; Rahmat Hasan; nFN Muzammil; nFN Rubiyo (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
ABSTRACT Influence of fertilization on soybean’s growth and yield in post-mined land in Central Banka. Ministry of Agriculture focuses to increase soybean production through extensification of  marginal lands such as tin post-mined land. However, the soil fertility is a limitation factor to optimize the marginal land. This study aimed to get an optimum rate of inorganic fertilizer for the growth and production of soybean at the tin post-mined land in Central Bangka. This research was conducted in tin post-mined lowland in the village of Perlang, Central Bangka district from June to September 2015. The study was arranged in a randomized block design (RAK) with inorganic fertilizer treatment dose level, which were urea 50 kg/ha, SP36 125 kg/ha and KCl 50 kg/ha (P1); urea 75 kg/ha, SP36 125 kg/ha and KCl 75 kg/ha (P2); urea 100 kg/ha, SP36 125 kg/ha and KCl 100 kg/ha (P3). The treatment was repeated nine times and it used Wilis soybean variety. The activities consisted of land preparation, early soil data collection, planting, fertilizer application dose treatment, maintenance, observation, harvest and post-harvest. The oberserved parameters were the chemical properties of the soil, growth and yield of soybean. Statistical data was analyzed with analysis of variance. The results showed that the rate of inorganic fertilizer did not significantly affect the plant growth of soybean but significantly affected on the soybeans yield. Fertilizer rate of 100-125-100 kg/ha (Urea-SP36-KCl) gave the highest yield, i.e. 1.16 tonnes/ha compared with the rate of 75-125 -75 kg/ha (Urea-SP36-KCl) and 50-125-50 kg/ha (Urea-SP36-KCl). Fertilization with the rate of 75-125-75 kg/ha Urea-SP36-KCl was the optimum rate in tin post-mined land for soybean crop since it gave the highest MBCR value, i.e. 7.76. fertilization, tin post-mined land, soybean ABSTRAK Kementerian Pertanian telah memfokuskan untuk meningkatkan produksi kedelai dengan ekstensifikasi ke lahan-lahan marginal. Optimalisasi lahan marginal terkendala oleh faktor kesuburan tanah yang rendah sehingga dibutuhkan tambahan pupuk organik dan anorganik. Pengkajian bertujuan untuk mendapatkan dosis pemupukan anorganik yang optimum untuk pertumbuhan dan produksi kedelai di lahan bekas tambang timah. Pengkajian dilakukan di Desa Perlang, Kabupaten Bangka Tengah dari Bulan Juni hingga September 2015, menggunakan rancangan acak kelompok (RAK) dengan perlakuan tiga taraf dosis pupuk anorganik: urea 50 kg/ha, SP36 125 kg/ha, KCl 50 kg/ha (P1); urea 75 kg/ha, SP36 125 kg/ha, KCl 75 kg/ha (P2); urea 100 kg/ha, SP36 125 kg/ha, KCl 100 kg/ha (P3). Perlakuan diulang sembilan kali dan menggunakan kedelai varietas Wilis. Pelaksanaan kegiatan meliputi persiapan lahan, pengambilan data tanah awal, penanaman, perlakuan dosis pemupukan, pemeliharaan, pengamatan, panen dan pasca panen. Parameter pengamatan adalah sifat kimia tanah, pertumbuhan dan hasil tanaman kedelai. Data dianalisis dengan analisis sidik ragam. Hasil pengkajian menunjukkan bahwa dosis pemupukan anorganik tidak berpengaruh nyata terhadap pertumbuhan tanaman namun berpengaruh nyata terhadap produksi tanaman kedelai. Dosis pemupukan 100-125-100 kg/ha (Urea-SP36-KCl) memberikan hasil tertinggi yaitu 1,16 ton/ha dibandingkan  dosis 75-125-75 kg/ha (Urea-SP36-KCl) dan dosis 50-125-50 kg/ha (Urea-SP36-KCl). Pemberian pupuk dengan dosis 75-125-75 kg/ha Urea-SP36-KCl merupakan introduksi teknologi pemupukan yang optimum untuk di terapkan di lahan bekas tambang timah pada tanaman kedelai dengan nilai MBCR tertinggi yaitu 7,76.lahan bekas tambang timah, pemupukan, kedelai